Development of Electronic Student Worksheets Based on Problem-Based Learning Assisted by Virtual Labs to Enhance Physics Students’ Creative Thinking Skills - Afrilia Putri, Mutiara (PILLAR OF PHYSICS EDUCATION, 2025)
Education in the 21st century requires students to acquire competencies aligned with the demands of an increasingly globalized world creative thinking. Several contributing factors were identified, including the minimal use of engaging instructional models and students’ excessive focus on digital devices. To address these challenges, this study aimed to develop an electronic student worksheet (E-LKPD) based on the PBL model and supported by virtual lab simulations, specifically targeting the topic of heat and temperature. This study employed a Research and Development (R&D) approach guided by the Plomp development model. The initial phase, or preliminary investigation, involved conducting a needs assessment, analyzing student characteristics, and reviewing relevant literature. In the prototyping phase, a preliminary version of the product was designed. -assessment by the researcher, The formative evaluation and revision process consisted of several stages: selfexpert validation, individual trials (one-to-one), and small group evaluations. The results of the study indicate that the E-LKPD achieved a validity score of 0.95 based on Aiken’s V index, placing it within the valid category. Among practicality students with varying ability levels-high, medium, and low-the E-LKPD attained an average practicality score of 90%, classified as very practical. In the small group trial, two physics teachers assigned an average score of 92%, while nine students from SMAN 1 Guguak provided an average score of 89%, both of which also fall under the very practical category